Compound Profile of Methanol Extract of Katang-Katang Leaves (Ipomoea pes-caprae) and Evaluation of Its Antibacterial and Antioxidant Activities - Dessy Rosye Rooy; Kapelle, Imanuel Berly Delvis; Rosmawaty (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2026)
Increasing antibiotic resistance has prompted the search for safer and more sustainable natural alternatives. Ipomoea pes-caprae, a coastal plant traditionally used for the treatment of wounds and inflammation, is known to be rich in secondary metabolites such as flavonoids, terpenoids, alkaloids, and phenolic acids that have potential antioxidant and antibacterial properties. This study aimed to map the metabolite profile of the methanolic extract of I. pes-caprae leaves using LC-HRMS, to analyze its relationship with antioxidant activity measured by the DPPH method, and to evaluate its antibacterial activity against Staphylococcus aureus and Escherichia coli. LC-HRMS analysis identified 406 compounds with Palmitic Acid as the dominant component (24.503%), including primary and secondary metabolite groups such as flavonoids (quercetin, rutin, kaempferol), phenolic acids (caffeic, ferulic, chlorogenic acid), terpenoids (caryophyllene oxide, lupeol), alkaloids, and phytohormones. The methanol extract showed moderate antioxidant activity (IC₅₀ = 136.71 ppm) and antibacterial activity against E. coli (inhibition zone 9.5 mm), which is thought to originate from the synergy of various secondary metabolites through free radical scavenging mechanisms and bacterial membrane damage. These findings strengthen the scientific basis for I. pes-caprae as a natural source of antioxidant and antibacterial agents for the development of natural pharmaceutical products.